Are P2Y12 reaction unit (PRU) and % inhibition index equivalent for the expression of P2Y12 inhibition by the VerifyNow® assay? Role of haematocrit and haemoglobin levels - Voisin, Sophie; Bongard, Vanina; Tidjane, Mohammed A.; Lhermusier, Thibault; Carrié, Didier; Sié, Pierre (Thrombosis and Haemostasis, 2011)
The results of the whole blood VerifyNow® P2Y12 assay can be expressed as platelet reaction units (PRU) or % inhibition index (%inh), but an optimal cut-off for the assessment of high on-treatment platelet reactivity (HPR) predictive of clinical events has been validated only for PRU. The aim of the study was to study the influence of haematological variables, such as platelet and leukocyte counts or haematocrit / haemoglobin, within the limits indicated by the manufacturer for assay validity, on the results of the test. We performed a comparison of PRU and %inh in a series 186 samples obtained from a clinical trial on patients under dual antiplatelet therapy. The results show that PRU significantly decreases with increasing haematocrit / haemoglobin, whereas %inh does not, due to a parallel change in PRU and iso-TRAP baseline value. PRU and % inhibition index are not equivalent for the definition of HPR, because of their different sensitivities to haematocrit / haemoglobin.
Keywords: VerifyNow® P2Y12 assay; haematocrit; haemoglobin